The Meaning of the King's Tomb in Penyengat Island, Riau Islands - Mukhlis, Suhardi; Husni, Alfi; Prastiyo, Endri Bagus; Ahadi, Ahadi (BELIEF: Sociology of Religion Journal, 2023)
The meaning of the King's tomb on Penyengat Island for pilgrims depends on their perception of the tomb itself. Perception is said to be recognition or identification using the five senses. The impression received by an individual is very dependent on all the experiences that have been gained through the process of thinking and learning and is influenced by factors originating from within the individual. The purpose of this research is to find out the meaning of the king's tomb in the community on Penyengat Island, Tanjungpinang City (Study on the Society of Penyengat Island City Tanjung Pinang). The theory used regarding meaning is phenomenology from Alfred Schutz. This research is qualitative research using interview and observation methods. Based on the research results, it can be concluded that the meaning of the King's tomb in the community on Penyengat Island, Tanjungpinang City, namely that the community interprets a King's tomb as something that must be respected. Moreover, this tomb is the tomb of a figure who was very instrumental in the development and progress of Penyengat Island, such as the tomb of Raja Ja'ffar, the tomb of Raja Ali Haji, the tomb of Engku Putri and the tombs of other figures